Discontinuous, conserved neutralization epitopes overlapping the CD4-binding region of human immunodeficiency virus type 1 gp120 envelope glycoprotein. - Thali, M (1992)
Monoclonal antibodies have been isolated from human immunodeficiency virus type 1 (HIV-1)-infected patients that recognize discontinuous epitopes on the gp120 envelope glycoprotein, that block gp120 interaction with the CD4 receptor, and that neutralize a variety of HIV-1 isolates. Using a panel of HIV-1 gp120 mutants, we identified amino acids important for precipitation of the gp120 glycoprotein by three different monoclonal antibodies with these properties. These amino acids are located within seven discontinuous, conserved regions of the gp120 glycoprotein, four of which overlap those regions previously shown to be important for CD4 recognition. The pattern of sensitivity to amino acid change in these seven regions differed for each antibody and also differed from that of the CD4 glycoprotein. These results indicate that the CD4 receptor and this group of broadly neutralizing antibodies recognize distinct but overlapping gp120 determinants.